Abandonment Issue in the Main Character of Joan G. Robinson's When Marnie Was There - Marita Inas Qonita; Prayudias Margawati (Rainbow: Journal of Literature, Linguistics and Culture Studies, 2025)
Family plays a critical role in shaping a child’s psychological development. An ideal family consists of each member fulfilling their assigned role. The absence of stability and love that a family offers can lead to long-term effects on children, especially if it happens to an infant. Joan G. Robinson’s When Marnie Was there explores the psychological struggles around children who experience separation from their primary caregiver and their inability to receive a secure environment. Therefore, this study aims to do an in-depth analysis on psychological problems of the main character who experience abandonment issue and what factors cause her to experience abandonment issue. This study uses qualitative methods by applying John Bowlby’s attachment theory and Carl Jung’s psychoanalytic theory, especially about insecure attachment. The novel shows how the abandonment issue was described and what factors cause it through the main character of the novel. The separation and instability that the main character experiences in her early childhood shapes how the main character perceives the world. It reflects Bowlby's attachment theory that psychological development of a person is shaped by what they experience in their infant phase, even if they can’t remember what happened and also represents Jung’s archetypes.